Generation of Tissue Factor by Patient Monocytes: Correlation to Thromboembolic Complications - Miller, Carol L; Graziano, Charles; Lim, Robert C; Chin, Milly (Thrombosis and Haemostasis, 1981)
Thromboembolic complications are often a common pathological consequence of severe soft tissue trauma. Recent demonstration that monocytes (MØ) produce tissue factor (TF) has led to the suggestion that these TF producing MØ might play a role in coagulopathy. We have previously demonstrated that trauma patients with splenectomy develop aberrant monocyte function and this patient group is also known to be at high risk of hypercoagulability episodes. This paper is an intial report on the use of MØ TF as an indicator of and/or a correlate to clotting episodes. Monocytes isolated from the Ficoll-Hypaque purified mononuclear cells of 46 normal individuals, 17 trauma patients and 6 surgical controls were assayed at 3 day post-injury intervals for their levels of TF activity. Changes in monocyte TF activity were correlated to increases in the fractional catabolic rate (FCR) of 125I-fibrinogen. Trauma patients were retrospectively divided into those whose FCR was elevated to a level indicative of coagulopathy and those whose FCR levels were not associated with coagulation abnormalites. All trauma patients who exhibited significantly increased FCR experienced thromboembolic episodes and had monocytes whose TF activity was increased an average of 300% (X = 47 units vs X = 12 units) over surgical controls. These increases in monocyte TF activity occrured at 6-13 days post injury and preceded clinical manifestation of coagulopathy by 4-6 days. The increased monocyte TF activity demonstrated in this study was significantly correlated to detection of pathologically increased FCR (Rs = 0.850) and compared to other indices of hypercoagulability.
Keywords: Monocyte; Procoagulant tissue factor (TF); Coagulopathy; Trauma